Interaction Between Barley Yellow Dwarf Virus-GAV Movement Protein and VOZ Proteins Delays Flowering of Plant - Yilin Zhang; Caiping Huang; Qiang Zeng; Ming Yang; Yanhong Wu; Ye Tao; Shafat Ahmad Ahanger; Hamza Rafiq; Yunfeng Wu; Xingan Hao (Molecular Plant-Microbe Interactions, 2025)
Dwarfing and yellowing are characteristic symptoms caused by viral infections and are considered significant contributors to reduced crop yield. In this study, we identified that infection by barley yellow dwarf virus-GAV (BYDV-GAV) leads to a delay in the flowering process, potentially diminishing grain yield in wheat. The BYDV-GAV movement protein (MP) interacts with vascular plant one-zinc finger proteins (VOZs), which play a crucial role in promoting wheat flowering. Expression of MP inhibits floral transition in Arabidopsis thaliana. Furthermore, BYDV-GAV MP facilitates the degradation of VOZ transcription factors via the 26S proteasome pathway, independently of phytochrome B. Domain B in VOZ is essential for the interaction between VOZ and MP. Our results provide novel insights into the molecular mechanisms underlying virus-induced symptoms. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.